Hyaluronan Synthase 1: A Mysterious Enzyme with Unexpected Functions - Siiskonen, Hanna; Oikari, Sanna; Pasonen-Seppänen, Sanna; Rilla, Kirsi (Frontiers in Immunology, 2015)
Hyaluronan synthase 1 (HAS1) is one of three isoenzymes responsible for cellular hyaluronan synthesis. Interest in HAS1 has been limited because its role in hyaluronan production seems to be insignificant compared to the two other isoenzymes, HAS2 and HAS3, which have higher enzymatic activity. Furthermore, in most cell types studied so far, the expression of its gene is low and the enzyme requires high concentrations of sugar precursors for hyaluronan synthesis, even when overexpressed in cell cultures. Both expression and activity of HAS1 are induced by pro-inflammatory factors like interleukins and cytokines, suggesting its involvement in inflammatory conditions. Has1 is upregulated in states associated with inflammation, like atherosclerosis, osteoarthritis, and infectious lung disease. In addition, both full length and splice variants of HAS1 are expressed in malignancies like bladder and prostate cancers, multiple myeloma, and malignant mesothelioma. Interestingly, immunostainings of tissue sections have demonstrated the role of HAS1 as a poor predictor in breast cancer, and is correlated with high relapse rate and short overall survival. Utilization of fluorescently tagged proteins has revealed the intracellular distribution pattern of HAS1, distinct from other isoenzymes. In all cell types studied so far, a high proportion of HAS1 is accumulated intracellularly, with a faint signal detected on the plasma membrane and its protrusions. Furthermore, the pericellular hyaluronan coat produced by HAS1 is usually thin without induction by inflammatory agents or glycemic stress and depends on CD44–HA interactions. These specific interactions regulate the organization of hyaluronan into a leukocyte recruiting matrix during inflammatory responses. Despite the apparently minor enzymatic activity of HAS1 under normal conditions, it may be an important factor under conditions associated with glycemic stress like metabolic syndrome, inflammation, and cancer.